Long-term sequelae of critical illness in sepsis, trauma and burns: a systematic review and meta-analysis - Haug, Valentin; Tapking, Christian; Panayi, Adriana C.; Thiele, Philipp; Wang, Alice T.; Obed, Doha; Hirche, Christoph; Most, Patrick; Kneser, Ulrich; Hundeshagen, Gabriel (The journal of trauma and acute care surgery, 2021)
BACKGROUND - Sepsis, major trauma, and severe burn injury are life-threatening critical illnesses that remain significant contributors to worldwide morbidity and mortality. The three underlying etiologies share pathophysiological similarities: hyperinflammation, hypermetabolism, and acute immunomodulation. The aims of this study were to assess the current state of long-term outcome research and to identify key outcome parameters between the three forms of critical illness. - METHODS - This systematic review and meta-analysis (MA) were conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. PubMed was searched from January 1, 1975, to December 31, 2019. Studies were assessed for eligibility by independent reviewers. Inclusion criteria were studies reporting at least a 6-month follow-up of health-related quality of life and organ-specific sequelae within the three etiologies: severe burn injury, sepsis, and major trauma. - RESULTS - In total, 125 articles could be included in the systematic review and 74 in the MA. The mean follow-up time was significantly longer in burn studies, compared with sepsis and trauma studies. The majority of patients were from the sepsis group, followed by burns, and major trauma studies. In the overall health-related quality of life, as assessed by Short Form 36 and European Quality-of-Life Index, the three different etiologies were comparable with one another. - CONCLUSION - The effects of critical illness on survivors persist for years after hospitalization. Well-reported and reliable data on the long-term outcomes are imperative, as they can be used to determine the treatment choice of physicians and to guide the expectations of patients, improving the overall quality of care of three significant patient cohorts. - LEVEL OF EVIDENCE - Systematic review and MA, level III.